Effective utilization of time for non –operating room anaesthesia services at Aga Khan University Hospital Karachi: a prospective quality improvement audit - Mohsin Nazir; Azhar Rehman; Rizwana shehzad; Tanveer Baig (Journal of the Pakistan Medical Association, 2022)
Objective: To identify service quality gaps by reviewing out-of-operating-room anaesthesia services in a tertiary care hospital. Method: This quality improvement audit was conducted at The Aga Khan University Hospital Karachi from July to September 2019, and comprised procedures conducted outside the operating room under anaesthesia and sedation from 8am to 5pm. A data collection form was designed to collect information related to the non-operating-room anaesthesia services. Data was analysed using SPSS Version 19. Results: A total of 123 radiological procedures were observed in 48 working days and endoscopic/radio-therapeutic procedures observed were 98 over 31 days. The mean anaesthesia coverage time was 2.96±1.71 hours per day for radiological procedures, and 2.59±1.07 hours for endoscopic/radio-therapeutic procedures, indicating underutlisation of resources both human and material . Conclusion:A multideciplinary team consisting of all stakeholders should be developed to facilitate the patients and enhance healthcare quality. Key Words: Non-operating-room anaesthesia, NORA, Radiological procedures, Monitored anaesthesia care, Multideciplinary team.